2022
DOI: 10.1007/s00167-022-07000-8
|View full text |Cite
|
Sign up to set email alerts
|

Early MRI-based quantitative outcomes are associated with a positive functional performance trajectory from 6 to 24 months post-ACL surgery

Abstract: PurposeQuantitative magnetic resonance imaging (qMRI) has been used to determine the failure properties of ACL grafts and native ACL repairs and/or restorations. How these properties relate to future clinical, functional, and patient‐reported outcomes remain unknown. The study objective was to investigate the relationship between non‐contemporaneous qMRI measures and traditional outcome measures following Bridge‐Enhanced ACL Restoration (BEAR). It was hypothesized that qMRI parameters at 6 months would be asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…However, translating these structural property prediction models to human patients and establishing their clinical relevance was necessary. In one of our studies, we showed that estimated failure load from Constructive Interference in Steady State scans (using a different prediction model) was significantly associated with functional outcomes for patients after the ACL restoration procedure 29 . To our knowledge, the present analysis is the first to show that the T 2 * relaxometry-based structural property predictions are associated with the incidence of revision surgery and is a critical step towards translating the large body of preclinical work that we have pursued.…”
Section: Discussionmentioning
confidence: 80%
“…However, translating these structural property prediction models to human patients and establishing their clinical relevance was necessary. In one of our studies, we showed that estimated failure load from Constructive Interference in Steady State scans (using a different prediction model) was significantly associated with functional outcomes for patients after the ACL restoration procedure 29 . To our knowledge, the present analysis is the first to show that the T 2 * relaxometry-based structural property predictions are associated with the incidence of revision surgery and is a critical step towards translating the large body of preclinical work that we have pursued.…”
Section: Discussionmentioning
confidence: 80%
“…Using qMRI parameters of ACLR crosssectional area, ligament volume, and estimated failure load, Flannery et al found that these measurements at 6 months were predictive of positive functional outcome at 24 months, suggesting that a larger, stronger ligament as determined by qMRI at 6 months indicates greater functional recovery over the following 18 months. 56 Upper Extremity, Meniscal, and Osseous Reinjury Shoulder Shoulder injuries are common in elite baseball athletes, tennis players, swimmers, and football quarterbacks. 57 The type of injuries that occur in each sport is unique with different rehabilitation periods and reinjury patterns after RTP.…”
Section: Correlation Of Clinical and Imaging Findingsmentioning
confidence: 99%
“…Using qMRI parameters of ACLR cross-sectional area, ligament volume, and estimated failure load, Flannery et al found that these measurements at 6 months were predictive of positive functional outcome at 24 months, suggesting that a larger, stronger ligament as determined by qMRI at 6 months indicates greater functional recovery over the following 18 months. 56…”
Section: Anterior Cruciate Ligament Reinjurymentioning
confidence: 99%
“…35,37,40,43 In addition, the surgically repaired tendon has a decreased risk of rerupture and an accelerated return to sport compared with nonoperative intervention. 31,37,40,43 Multiple operative interventions for Achilles repair are available, including open and minimally invasive procedures. Both open and minimally invasive repairs involve suturing the tendon back together; however, whereas in an open repair the tendon fibers can be sutured directly together, particularly if the tear is small, minimally invasive repair does not involve a direct end-to-end repair.…”
Section: Achillesmentioning
confidence: 99%
“…Using a constructive interference in steady state sequence, studies have demonstrated an ability to calculate a cross-sectional area and volume of the ACL graft, both of which were shown to correlate with a positive change in single-hop ratio results from 6 to 24 months. 31 Although such techniques require time-intensive segmentation of the graft with specialized software, it suggests additional data that MRI can provide in the prognostication and determination of RTP.…”
mentioning
confidence: 99%